Genetic recombination in cancer - Sherbet, G. V (Academic Press, 2003)
Genetic recombination is a process of combining genes that leads to the generation of cell variants that possess different characteristics. This process is important to the evolution of a species and to embryonic growth and differentiation. However, this process can also lead to the development of abnormal, cancerous cells. This book reviews the role of genetic recombination in the generation of various cancers and how genetic alterations have been or could be employed to elicit clinically useful information. * Provides detailed discussion of the genetic mechanisms that result in the generation of normal and abnormal cells* Examines the role of genetic recombination in cancer including cancer invasion and metastasis* Information is presented in a manner that is useful and accessible to everyone from graduate students to established cancer researchers
Keywords: Neoplasms; biologie; nádory; Recombination, Genetic; replikace DNA; DNA Replication; rekombinace genetická; chromozomální aberace; Chromosome Aberrations; onkologie